Chlorophyll-based wicking sensing bioplatform coupled with a smartphone-based sample-to-answer analytical device for on-site detection of picric acid - Maryam Shafizadeh; Samira Abbasi-Moayed; Zohre Hamzei; Azarnoosh Keshavarz; Sarah Yousefi; Mohammad Reza Hormozi-Nezhad; Hamed Golmohammadi (Biosensors and Bioelectronics: X, 2022)
The development of inexpensive, equipment-free, portable, and user/environmentally-friendly analytical devices that can be efficiently utilized for on-site detection of PA is still a great challenge. To address these unmet demands, we have developed a smartphone-based disposable sensing bioplatform through immobilization of chlorophyll in a cotton thread for fluorescent monitoring of picric acid (PA). The fluorescence quenching of chlorophyll upon increasing the PA concentration based on the inner filter effect was considered as the sensing strategy in the developed sensor. The fabricated thread-based microfluidic sensing bioplatform was further coupled with a compact, low cost, portable, and 3D-printed all-in-one smartphone-based analytical device (ASAD) that is able to thoroughly perform all analytical steps of PA determination in environmental samples, including sample preparation (mixing and centrifuging/separating) and analyzing steps. The satisfactory results achieved by the fabricated ASAD-based wicking sensing platform with good linearity (5.0–100.0 μM), detection limit (1.0 μM), and selectivity toward PA show its great potential to be widely exploited for easy, ultra-low-cost, sensitive, selective, and smart detection of PA, particularly at point-of-use applications, where are often far from well-equipped centralized laboratories.